Atmospheric Oxidation and Toxicity Evolution of Chlorobenzotrifluoride from Solvent-Based Paints: Implications for Environmental and Health Risk Assessment - Zihao Fu; Song Guo; Petri Clusius; Putian Zhou; Zeqi Cui; Robin Wollesen de Jonge; Siddharth Iyer; Wei Nie; Maosheng Yao; Min Hu; Michael Boy (Environment & Health, 2026)
Abstract Chlorobenzotrifluoride (PCBTF) is a high-production-volume solvent widely used in solvent-based paints and coatings and represents an important source of volatile chemical product (VCP) emissions. Here, we investigate the OH-initiated atmospheric oxidation of PCBTF under high-NO (outdoor) and low-NO (indoor) conditions. Quantum chemical calculations combined with kinetic modeling reveal a previously unrecognized concerted RO2·- and RO·-mediated autoxidation mechanism that efficiently forms highly oxygenated, low-volatility oxidation products. A key mechanistic finding is a peroxide-bridged cyclic RO2· rearrangement pathway together with distinct substituent effects of the −CF3 and −Cl groups on bicyclic radical reactivity. Incorporation of the explicit mechanism into a chemistry-aerosol box model predicts substantial formation of semivolatile and low-volatility oxidation products, with strong dependence on NO conditions. Computational toxicology further indicates that many oxidation products are more toxic than the parent PCBTF. Time-resolved simulations show that health risks peak during the first week after PCBTF release, while several toxic products persist for up to two months in indoor environments. Collectively, this study establishes a mechanistic framework linking VCP oxidation chemistry with volatility evolution and toxicity, enabling improved assessment of exposure risks associated with solvent-based paint emissions in indoor and outdoor environments.